Overview of systematic reviews - a new type of study. Part I: why and for whom? - Silva, Valter; Grande, Antonio José; Martimbianco, Ana Luiza Cabrera; Riera, Rachel; Carvalho, Alan Pedrosa Viegas (São Paulo Medical Journal, 2012)
CONTEXT AND OBJECTIVE: Healthcare decision-making is complex and should involve healthcare professionals, patients and the best level of evidence. The speed of information production creates barriers against keeping up to date. In this light, methodologists have proposed a new type of study: overviews of systematic reviews (OoRs). The aim here was to introduce and demonstrate the role of OoRs in information synthesis for healthcare professionals, managers, researchers and patients. DESIGN AND SETTING: Time-series study conducted at the Brazilian Cochrane Center, jointly with the Postgraduate Program on Internal Medicine and Therapeutics, Discipline of Emergency Medicine and Evidence-Based Medicine, Department of Medicine, Federal University of São Paulo. METHODS: To show the growth in the numbers of published papers that provide high-level evidence and thus demonstrate the importance of OoRs for synthesis and integration of information, three filters for study designs were applied to two databases. An equation for predicting the expected number of published papers was developed and applied. RESULTS: Over the present decade, the number of randomized controlled trials in Medline might reach 2,863,203 and the number of systematic reviews might reach 174,262. Nine OoRs and 15 OoRs protocols have been published in the Cochrane Library. CONCLUSIONS: With the exponential growth of published papers, as shown in this study, a new type of study directed especially towards healthcare decision-makers was proposed, named “overview of systematic reviews”. This could reduce the uncertainties in decision-making and generate a new hierarchy in the pyramid of evidence.